REORIENTASI PENDANAAN PENDIDIKAN DALAM MEMBANGUN MUTU SEKOLAH - Badrut Tamam (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2018)
Education has a very important role in the development of human capital. It affects the economic growth of a nation. Moreover, education is not only affect the productivity but also the creativity of the society. In improving the quality of Indonesian people, the government should be able to stand in a synergized system with the private sector and also the society itself, especially the parents. The relationship between government, private sector, and the parents is an integral part in improving the equality and quality of education. The classic problems that are often encountered by the educational institutions in this country are the equality of education and also education funding which are not optimal enough in its realization. The education funding is one of the important components that affect the quality of the education itself. A survey revealed that: the implementation of education could not run properly without the cooperation of the central government, local government, and the society in behalf to provide the optimum education funding system.